2021
DOI: 10.3390/diagnostics11081327
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Interleukin-6 among Several Inflammatory Markers as a Predictor of Respiratory Failure in COVID-19 Patients

Abstract: Patients with coronavirus disease 2019 (COVID-19) develop severe respiratory failure within a short period during the clinical course. It is essential to predict respiratory deterioration in the short term. We investigated the use of inflammatory markers to predict respiratory distress within three days from their analysis in COVID-19 patients. This retrospective observational study included 81 patients admitted with COVID-19. Patients were divided into two groups according to whether the maximum fraction of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Most investigations regarding IL-6 in SARS-CoV-2 infection have demonstrated that IL-6 increases prior to ARDS in critical COVID-19 patients (35) and that elevated IL-6 levels were predictors of the need for mechanical ventilation (40). Our results are in line with those studies in the context of severity of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most investigations regarding IL-6 in SARS-CoV-2 infection have demonstrated that IL-6 increases prior to ARDS in critical COVID-19 patients (35) and that elevated IL-6 levels were predictors of the need for mechanical ventilation (40). Our results are in line with those studies in the context of severity of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…Our cohort was initially classified into moderate and severe patients, distinguishing two groups in the latter category, severe survivors and severe non-survivors. Similar to recent studies, our data showed that IL-6 was significantly increased in severe groups (35). However, the levels of IL-6 were lower compared to those observed in sepsis (983 pg/mL), in non-COVID ARDS (460 pg/mL), and in CAR-T CRS (3110 pg/mL) (36), suggesting that the systemic inflammation during COVID-19 is less robust (37)(38)(39).…”
Section: Discussionsupporting
confidence: 90%
“…Clinical and phenotypical characteristics of COVID-19 patients were compared by categorical variables or by the median values of continuous variables. For this last purpose, the reference values of IL-6 and LDH considered in our design are compatible with previous reports exploring laboratory predictors and prognostic factors of severe COVID-19 disease concerning respiratory functions [ 10 , 11 ] as well as pharmacological prescription making decision criteria [ 12 ]. Moreover, Chi-square and unpaired Student's t -tests were applied for the univariate analysis.…”
Section: Methodssupporting
confidence: 73%
“…The level of CRS-related cytokine IL-6 in COVID-19 patients is gradually increased with the increasing severity ranging from asymptomatic cases to mild and severe cases [76] , [92] . Similarly, the correlation between the IL-6 level and metabolites increases with the increasing disease severity.…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 98%
“…4 ). Thus, IL-6 acts as a pivotal inflammatory factor triggering CRS in COVID-19 patients, which can be used to effectively assess the disease severity and predict prognosis of COVID-19 patients [90] , [91] , [92] . Recent clinical trials have shown that tocilizumab could suppress hyperactive immune response, improving the inflammatory symptoms of patients with or without mild organ damage at the early stage of COVID-19 [86] , [88] , [93] .…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%